Building Patience Character in Elementary Students through Prophet Yusuf’s Story: Membangun Karakter Kesabaran pada Siswa Sekolah Dasar Melalui Cerita Nabi Yusuf - Cahyono, Eko; astutik, anita puji (Indonesian Journal of Education Methods Development, 2025)
General Background: Bullying, as a persistent form of intentional oppression and violence, has become an escalating problem in schools, negatively affecting students’ academic and social development. Background (Specific): In the elementary school context, children often lack the resilience to face bullying, thus requiring character education rooted in moral and religious values. Knowledge Gap: Previous studies have explored patience in Islamic teachings generally, yet limited research has contextualized the story of Prophet Yusuf as a medium to cultivate patience specifically in addressing bullying among elementary students. Aim: This study seeks to examine whether the story of Prophet Yusuf can foster patience in 5th grade students at SDN Tales 2 in responding to bullying. Results: Using qualitative methods through interviews, observations, and documentation, findings reveal that storytelling about Prophet Yusuf inspires students to endure bullying experiences with patience and refrain from retaliation. Novelty: The integration of Qur’anic narratives into character formation provides a contextual and practical approach to reducing negative behaviors in schools. Implications: The study suggests that incorporating religious storytelling in educational settings not only enriches moral education but also offers an effective strategy for fostering resilience and patience in young learners against bullying. Highlights: Story of Prophet Yusuf fosters patience against bullying. Religious storytelling strengthens character education in elementary schools. Novel approach links Qur’anic values with anti-bullying strategies. Keywords: Character Formation, Patience, Bullying, Elementary Students, Prophet Yusuf